2004
DOI: 10.1007/s00216-003-2313-3
|View full text |Cite
|
Sign up to set email alerts
|

Iodine concentration in different human brain parts

Abstract: Iodine is one of the most important essential elements as demonstrated by the fact that its deficiency can cause goitre. Nevertheless, quantitative data on its concentration in biological materials, especially in the human brain, are scarce. There is therefore a demand for accurate and reliable information on iodine in these types of samples. The purpose of the present work was to determine the concentration of total iodine in some control human brain parts by rapid radiochemical neutron activation analysis. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…The nature and site of iodine binding in the human brain is still unknown. The results of Andrasi et al (Andrási et al, 2004) investigations on iodine distribution between the lipid fraction and in the brain tissue without lipid have indicated that its mean contents vary between 910 ± 147 ng/g dry weight and 281 ± 68 ng/g dry weight depending on the brain region (the highest content was found in susbstantia nigra and the lowest in vermis crebelli).…”
Section: Brainmentioning
confidence: 98%
“…The nature and site of iodine binding in the human brain is still unknown. The results of Andrasi et al (Andrási et al, 2004) investigations on iodine distribution between the lipid fraction and in the brain tissue without lipid have indicated that its mean contents vary between 910 ± 147 ng/g dry weight and 281 ± 68 ng/g dry weight depending on the brain region (the highest content was found in susbstantia nigra and the lowest in vermis crebelli).…”
Section: Brainmentioning
confidence: 98%
“…hyperintense on T1W and hypointense on T2W). These structures are very metabolically active and contain large amounts of iodine [83] and so may be more susceptible to insults caused by ID. Additionally, Alves et al [68] found hyperintense white matter in the anterior and posterior forceps, splenium and frontal lobes on T2W MRI.…”
Section: Location Of the Abnormalitiesmentioning
confidence: 99%
“…A detection limit of about 200 ng g -1 was attained at the analysis of biological samples by instrumental NAA with epithermal neutrons (EINAA) using a relatively low neutron flux reactor [6], and it could be lowered to about 20 ng g -1 if combined with a Compton suppression counting system [7]. Using radiochemical NAA (RNAA), even better detection limits could be obtained (down to ng g -1 level) [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%